POLA KOMUNIKASI PENYELESAIAN KONFLIK PENDIRIAN GEREJA YASMIN BOGOR - Fakhrudin (Departemen Komunikasi dan Penyiaran Islam, 2023)
Conflict is a social phenomenon that is present in social life, so that conflict is inherently means conflict will always exist in every space and time, anywhere and anytime. In this view, society is an arena of conflict or an arena of conflict and integration that is always going on. Therefore, conflict and social integration is a symptom that always fill every social life. Things that encourage the emergence of conflict and integration is the existence of similarities and differences of social interests . In every social life there is not a single human having the exact similarity, whether of ethnicity, interests, will, will, purpose and so on. From each conflict there are some that can be resolved, but some can not be resolved resulting in some acts of violence. Violence is a symptom that can not overcome the root of the conflict, causing violence from the smallest model of violence to war. Good communication is needed in problem solving and is important in achieving the success of a life in the community.Conflicts can be resolved well if communication is harmoniously established between the community, both verbal and non verbal. Effective communication patterns are one of the most important conditions in relation to resolving conflicts among conflict resolution societies that arise in marriage life especially in different national marriages, the subject of education because women and men are distinctly different in terms of communication. This is what then makes researchers want to know more deeply about how the picture polakomunikasi in conflict resolution Keywords: Patterns, Communication, and Conflict.